2020
DOI: 10.1186/s12916-020-01827-z
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity, polypharmacy, and drug-drug-gene interactions following a non-ST elevation acute coronary syndrome: analysis of a multicentre observational study

Abstract: Background The number of patients living with co-existing diseases is growing. This study aimed to assess the extent of multimorbidity, medication use, and drug- and gene-based interactions in patients following a non-ST elevation acute coronary syndrome (NSTE-ACS). Methods In 1456 patients discharged from hospital for a NSTE-ACS, comorbidities and multimorbidity (≥ 2 chronic conditions) were assessed. Of these, 698 had complete drug use recorded at discharge, and 652 (the ‘interaction’ cohort) had drug use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Several medications prescribed for the prevention and treatment of diseases of the cardiovascular system are highly interactive ( Table 1 ). Moreover, multi-morbidity is linked with the high prevalence of polypharmacy ( Turner et al., 2020 ). Accordingly, it is not unusual for older patients with atherosclerosis-associated ischemic heart failure to receive a sizeable combination of cardiovascular therapeutics, e.g., heart failure drugs like digoxin, a cholesterol-lowering drug like simvastatin, one or more blood pressure (BP)-lowering drugs like an angiotensin-converting enzyme inhibitor (ACEI), angiotensin II receptor blocker (ARB), beta blocker, and/or diuretic, and an antiplatelet like aspirin and an anti-coagulant such as warfarin or clopidogrel ( Turner et al., 2020 ).…”
Section: Polypharmacology Pharmacogenomics and Pharmacointeractomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several medications prescribed for the prevention and treatment of diseases of the cardiovascular system are highly interactive ( Table 1 ). Moreover, multi-morbidity is linked with the high prevalence of polypharmacy ( Turner et al., 2020 ). Accordingly, it is not unusual for older patients with atherosclerosis-associated ischemic heart failure to receive a sizeable combination of cardiovascular therapeutics, e.g., heart failure drugs like digoxin, a cholesterol-lowering drug like simvastatin, one or more blood pressure (BP)-lowering drugs like an angiotensin-converting enzyme inhibitor (ACEI), angiotensin II receptor blocker (ARB), beta blocker, and/or diuretic, and an antiplatelet like aspirin and an anti-coagulant such as warfarin or clopidogrel ( Turner et al., 2020 ).…”
Section: Polypharmacology Pharmacogenomics and Pharmacointeractomesmentioning
confidence: 99%
“…Genetic factors may contribute to the vulnerability to and impacts of DDI in patients with one or multiple diseases, largely through the regulation of the DDI biological responses. Genetic polymorphisms have been demonstrated in genes coding for drug metabolizing processes, including cytochrome P450 ( Turner et al., 2020 ), or transporting proteins, such as p-glycoprotein ( Holtzman et al., 2006 ) and organic cation transporter (OCT) ( Zhou et al., 2021 ).…”
Section: Polypharmacology Pharmacogenomics and Pharmacointeractomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor to consider is that as our population continues to age, the prevalence of multimorbidity will increase ( Uijen and van de Lisdonk, 2008 ), which will be accompanied by polypharmacy. Multimorbidity and polypharmacy increase the likelihood of drug- and gene-based interactions ( Turner and et al, 2020 ). The elderly are liable to be prescribed NSAIDs, including LDA, because of the high prevalence of cardiovascular disease and arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric patients, for example, the annual prescribing prevalence of at least one level A drug (recommendations for drugs available with high evidence regarding a particular genotype) ranges from 7987 to 10,629 per 100,000 patients [6]. Turner analyzed the data from non-ST elevation myocardial infarction patients (n = 1456) and found that 98.7% of the patients had at least one actionable genotype [7]. Within the interaction cohort (drug use and actionable genotypes available), 882 interactions were identified in 503 patients (77.1%), of which 346 interactions in 252 patients (38.7%) were substantial: 59.2%, 11.6%, 26.3%, and 2.9% substantial interactions were DDIs, DGIs, Drug-Drug-Gene-Interactions (DDGIs) and Drug-Gene-Gene-Interactions (DGGIs), respectively (see Table 1 for definitions).…”
Section: Intoductionmentioning
confidence: 99%